Funkcja prahistorii we współczesnym społeczeństwie - Kmieciński, Jerzy (Acta Universitatis Lodziensis. Folia Archaeologica, 1982)
Prehistoric studies conducted all over the world made it possible to unearth preliterate cultures and discover a big diversification of civilizations created by man.Prehistory made us aware that all people irrespective of the age of their cultural status can document their past by millions of fossil findings. Thanks to the prehistory man with his material apparatus of technique, his self-knowledge in such fields as ethics, religion, or philosophy may be analyzed as a result of the evolutional process, which for a long time has been understood as changes in other forms of life. A difference between man and animal was revealed in the process of assimilating and processing the nature by him. The idea of work, which thanks to prehistory may have been encompassed by a philosophical formula, constitutes a fundamental princuple describing both the character and genesis of human existence.Prehistory opens up a deep historical perspektive of understanding the world. Since it was included in to a search for origins and determination of human beings’ identity it has become possible to extend the historical awareness far back in to prehistoric times. Throughout most of the existence of human history the space of territorial and historical awareness was narrowly limited. Thus it is not surprising that only a few decades earlier the ancient history as seen by Europeans was synonymous with the history of Biblical and classical man; history of the Middle Ages - was treated as synonymous with history of crusades , while modem times with history of European states and their colonies.Today there is a need for a comprehensive approach to the past history allowing to accomodate experiences of different civilizations. Thus one’s own prehistory must be analyzed against the background of other territories and human groups. It should, however, be characterized with respect for the native cultural tradition.The eminent place of prehistory consists in the fact that it represents the only science being able to reach far back in to the times about which we do not have any written records, and also - or perhaps primarily - because it is a science about continuously progressing development of man.